THE ROLE OF CLASS TEACHER’S PROXIMITY IN DEVELOPING LEARNERS' SELF-CONFIDENCE AT INDONESIAN SCHOOL IN KUALA LUMPUR MALAYSIA - Ariyanti, Dwi; Farisia, Hernik (Universitas Islam Negeri Mataram, 2024)
Learners' self-confidence is an important concern for teachers to ensure the continuity of the learning process. Indonesian School of Kuala Lumpur builds learners' self-confidence one of them by emotional approach. This research aims to (1) describe how the proximity of class teachers and learners at Indonesian School of Kuala Lumpur, and (2) explain the role of class teachers' proximity in developing learners' self-confidence at Indonesian School of Kuala Lumpur. This type of research is qualitative research with a case study approach. The research subjects were class teachers and learners of Sekolah Indonesia Kuala Lumpur (SIKL) at the elementary school level. The type of data used is primary data. Data collection techniques were observation, in-depth interviews, and documentation. The data were analyzed using the Miles & Huberman data analysis technique. Data validity techniques used triangulation of sources, methods, and data. The results showed that the proximity between class teachers and SIKL learners was excellent and closely intertwined. In addition, SIKL learners have a high level of self-confidence with indicators of courage, activeness, comfort, and enthusiasm. Thus, it’s important to build proximity between class teachers and learners to develop their self-confidence. This research suggests that class teachers should be able to build proximity with learners so that their self-confidence can develop well, and therefore have a good impact on their learning outcomes.